I have a problem which reads: A frictionless pulley with zero mass is attached to the ceiling, in a gravity field of 9.81 m/s2 . Mass M2 = 0.10 kg is observed to be accelerating downward at 1.3 m/s2 and I have a solution which tells me to solve the problem use Newton's 2nd law: m1a1 = T1 - m1g m2a2 = T2 - m2g We also have an acceleration (constraint/constant??) a1 = a2 = a, and by Newton's 3rd law, T1 = T2 => m1 (a+g) = m2 (g-a) => m1 = [(g - a)/(g + a)]m2 and then from this we just plug in numbers. My question is, how do we arrive to the conclusion of creating this equation? I'm really confused about how to actually set up the equation. Also is a1 and a2 the same acceleration just in opposite directions?